Transcarotid artery revascularization (TCAR): a technical video. (2nd September 2021) - Sujijantarat, Nanthiya; Antonios, Joseph; Koo, Andrew; Renedo, Daniela; Cord, Branden J; Zetchi, Akli; Hebert, Ryan; Matouk, Charles
Abstract : Carotid revascularization is an important method of stroke prevention and includes carotid endarterectomy and transfemoral carotid angioplasty and stenting. More recently, a hybrid open-endovascular approach, termed transcarotid artery revascularization (TCAR), is garnering increased attention. Although fundamentally a 'stenting procedure', unlike transfemoral carotid angioplasty and stenting, TCAR allows for a proximal neuroprotection strategy based on flow reversal. In this technical video, we will review operative techniques and nuances of the TCAR procedure, with a particular focus on the neurovascular proceduralist looking to adopt this technique into routine clinical practice( video 1 ).